Diversity of Aphyllophorales fungi from dang forest region of Nashik, Maharashtra, India (International Journal of Food and Nutritional Sciences, 2022)
The authors of the current study gathered a large number of fungal specimens from Nashik Dang Forest inthe western ghat of Maharashtra and Gujarat. The goal of the current study is to map the variety anddistribution of native Aphyllophorales in this forest, which is related to Karnjul, Surgana, Peth, Umbarthan,and Borgoan. The present study was conducted from July to October 2022, throughout the rainy and earlydry seasons, samples were taken from both low and high altitudinal ranges. Various locations within theforest research area were examined and utilized to gather a variety of fungal specimens. TheAphyllophorales species viz. Pinophora sps., Ganoderma sp., Hexagonia sp., Microporus sp., Phellinassp., and Flavolus sps. were identified based on Macroscopic and microscopic features and use key for thisidentification. The early dry season saw the most abundance of species Ganoderma and Microporous sp.among these species. The study showed that the Aphyllophorales diversity has observed. The dang regionrequired for conservation efforts, particularly for species that are edible and therapeutic.